Understanding aerosol formation mechanisms in a subtropical atmosphere impacted by biomass burning and agroindustry - Souza, Michele L. [UNESP]; Allen, Andrew G. [UNESP]; Cardoso, Arnaldo A. [UNESP] (Elsevier, 2017)
This work provides evidence for the existence of strong seasonality in homogeneous and heterogeneous aerosol formation in a subtropical region affected by agricultural biomass burning. Acquisitions of aerosol size distributions were made in central Sï¿½o Paulo State between August 2011 and November 2012, using a scanning mobility particle sizer (SMPS) system. Aerosols were also collected using a high volume impactor for analysis of major ions in the <ï¿½0.49ï¿½μm size fraction. The SMPS data were grouped into three size fractions: <ï¿½25ï¿½nm, 25–100ï¿½nm, and 100–615ï¿½nm, which were used to represent the nucleation, Aitken, and lower accumulation mode size ranges, respectively. Different aerosol types and atmospheric conditions were shown to influence the relative contributions of the different aerosol size fractions and their interrelationships. The total number concentrations of particles in the nucleation size range varied between 4.03ï¿½× 10−ï¿½3 and 5.18ï¿½× 104ï¿½cm−ï¿½3, concentrations in the Aitken size range varied between 1.60ï¿½× 101 and 3.17ï¿½× 104ï¿½cm−ï¿½3, and concentrations in the accumulation size range varied between 0.00 and 6.67ï¿½× 103ï¿½cm−ï¿½3. Distinct seasonal differences in particle formation were observed, with evidence for the preferential occurrence of homogeneous nucleation during the wetter summer months and heterogeneous nucleation during the winter when there were strong emissions from biomass burning. Homogeneous nucleation of new particles was inhibited in the winter, due to the greater surface area of existing aerosols available for the uptake of reactive gases. Consequently, the nucleation and Aitken modes were favored in the wet (summer) and dry (winter biomass burning) periods, respectively. The accumulation mode showed peaks in the summer and winter, which could be explained by hygroscopic particle growth and heterogeneous reactions, respectively.
Keywords: Aerosols; Agro-industry; Heterogeneous processes; Homogeneous nucleation; Size distribution